Metal complexes of anti-tubercular drugs - Dauda, Khadijah Tolulope (Department of Chemistry, 2018)
There is a continuing need to improve anti-tubercular drugs due to the development of resistance towards existing drugs. In some cases, metal complexes are known to improve the bioavailability of drugs. Hence the present study looks at the use of metal complexes of anti-tubercular drugs to improve the permeability and bioavailability of the drugs. The anti-tubercular drugs isoniazid (ISO), ethambutol (EMB), para-aminosalicylic acid (PAS), rifampicin (RFN) and pyrazinecarboxamide (PZA) were used in this study. Since the solubility and hence permeability and bioavailability of the drugs depend on their solution speciation, the equilibrium constants for the reaction of H+ , Cu(II), Ni(II) and Zn(II) with the ligands were measured, in aqueous solution, at 25  0.01C and an ionic strength of 0.15 M (NaCl) using glass electrode potentiometry. The structures of the complexes with EMB, ISO and PAS were investigated using ultravioletvisible spectroscopy. The visible spectra obtained for the different species of EMB in solution were typical of Cu(II) and Ni(II) complexes. The spectra found for the various species of ISO and PAS in solution were also characteristic of their Cu(II) complexes. The results from the visible spectra support the structures postulated from the potentiometric data. This study also considered membrane permeability and absorption using a Franz cell and octanol/water partition coefficients. Partition coefficient studies showed that ISO and PZA and their complexes are hydrophilic while RFN and PAS and their complexes are lipophilic. The incorporation of a metal-ion improves the lipophilicity/hydrophilicity properties of the ligand. The presence of metal greatly enhanced the permeation of ISO through an artificial membrane in the order Cu(II) > Zn(II) > Ni(II) > ISO. A significant improvement was also found when Cu(II) was incorporated into the RFN system with an enhancement factor of 20. Zn(II) was vii able to improve the permeation of PAS with an enhancement ratio of 2. The incorporation of Cu(II), Ni(II) and Zn(II) does not affect the flux and permeability coefficient of PZA. Since the drugs are administered in tablet form, attempts were made to synthesise the metal complexes of the drugs in solid form. X-ray crystallography could then be used to confirm the solution structures. Co-precipitation, refluxing and mechanochemical methods (neat and liquid-assisted co-grinding) were employed to synthesise Cu(II), Ni(II) and Zn(II) complexes of the series of anti-tubercular drugs. However, despite exhaustive efforts, all experiments resulted in the formation of only physical mixtures of the reactants, as revealed by chromatographic and X-ray diffraction methods. This impelled the use of the solvothermal method as an alternative technique. ISO and PZA metal complexes were synthesised via this method. Unexpected products were obtained, as indicated unambiguously by single crystal Xray diffraction, and a probable mechanism for their formation was postulated. The incorporation of metals into anti-tubercular drugs has a significant influence in improving the permeability of the parent drug. It was found that the presence of Cu(II), Ni(II) and Zn(II) improved the permeability coefficient of ISO, while Cu(II) improved RFN and Zn (II) enhanced that of PAS.